2023
DOI: 10.1186/s12913-023-10065-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mother's healthcare-seeking behavior for symptoms of acute respiratory infection in under-five children in sub-Saharan Africa: a multilevel robust Poisson regression modelling

Getayeneh Antehunegn Tesema,
Beminate Lemma Seifu

Abstract: Background Timely and appropriate treatment for childhood illness saves the lives of millions of children. In low-middle-income countries such as sub-Saharan Africa (SSA), poor healthcare-seeking behavior for childhood illnesses is identified as a major contributor to the increased risk of child morbidity and mortality. However, studies are limited on Factors associated with mother's healthcare-seeking behavior for symptoms of acute respiratory infection in under-five children in sub-Saharan Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Similarly, it has been demonstrated that mothers who are educated are more likely to have healthcare-seeking behavior for ARIs. This result is also consistent with research carried out in Ethiopia ( 14 , 17 , 45 ). Mothers who have completed primary school or higher are more likely to seek medical attention and remedies for their children, as well as to take better care of them ( 46 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, it has been demonstrated that mothers who are educated are more likely to have healthcare-seeking behavior for ARIs. This result is also consistent with research carried out in Ethiopia ( 14 , 17 , 45 ). Mothers who have completed primary school or higher are more likely to seek medical attention and remedies for their children, as well as to take better care of them ( 46 ).…”
Section: Discussionsupporting
confidence: 93%
“…The WHO is working on improving preventable child deaths and improving access and quality of care for newborns and children in primary healthcare services ( 13 ). Still, the goal of the integrated management of childhood illness (IMCI) program, which was introduced in low- and middle-income countries (LMICs), particularly in SSA, has not been met ( 14 ). Several studies on healthcare-seeking behavior for symptoms of ARIs among children under the age of 5 have been conducted in Bangladesh, Nigeria, east Africa, rural Kenya ( 15 ), Ghana, and sub-Saharan Africa ( 7 , 11 , 14 , 16–19 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation